Role of Vitrectomy in the Management of Eales? Disease - Javed Hassan Niazi, Asfandyar Asghar (Pakistan Journal of Ophthalmology, 2007)
Purpose: To study the visual outcome and complications after pars plana vitrectomy in Eales’disease. Patients and Methods: Patients were admitted from the outpatients department at Jinnah Postgraduate Medical Centre, Karachi, from November 2001 up to May 2002. Patients were diagnosed as Eales’ disease after all causes of ocular and systemic vasculitis had been ruled out on the basis of history, clinical examination and laboratory investigations. Patients with non-resolving vitreous hemorrhage, recurrent vitreous hemorrhage, fresh vitreous hemorrhage in only eye patients, combined tractinal and rhegmatogenous retinal detachment were included in the study. Patients with past history of trauma to the eye, ocular surgery, corneal opacity, rubeosis iridis, glaucoma were excluded from the study. Result: 10 eyes of patients were included. Mean age of presentation was 27.75 years. Male to female ratio were 4:1. Most common presentations were non– resolving vitreous hemorrhage in 7 eyes (70%), combined tractional and rhegmatogenous retinal detachment in 2 eyes (20%) and tractional retinal detachment in 1 eye (10%). Pre-operative visual acuity in all patients was perception of light to counting finger. 90% of eyes regained good visual acuity after pars plana vitrectomy i.e. 0.2 (6/30) or better, after follow up period of 6 months. Per-operative complications included active bleeding in 3/10 cases and sub-retinal seepage of perflurocarbon liquid in 1/5 cases. Post-operative complications included cataract in 2/7 cases, secondary glaucoma in 2/7 cases, rhegmatogenous retinal detachment in 2/10, emulsifications of silicone oil in 3/7 cases and pre-retinal membrane formation in 1/7 cases. Conclusion: In Eales’ Disease, uncomplicated pars plana vitrectomy has shown improvement of visual acuity in majority of patients.